Isolated Polymer Chain in a Random Medium - Cherdsak Kunsombat (Agriculture and Natural Resources, 2010)
A model of an isolated polymer chain in a random medium was investigated. The model was extended from a model using a Gaussian correlation function and was solved in three spatial dimensions using the path-integral method. The polymer propagator and the mean squared end-to-end displacement of a chain were derived, respectively. It was shown that the properties of a polymer depended on the correlation length, the fluctuation magnitude and the density of the random medium. The results from this model were reduced to the results from the model using the Gaussian correlation function when the parameter Ω approached zero.